USING OF NEGATIVE WOUND PRESSURE THERAPY (NPWT): A CASE SERIES OF WOUND DISRUPTION AS A COMPLICATION OF A CAESAREAN SECTION - Herman Yosef Limpat Wihastyoko; Ellenora Resti Mustikaningrat; Dorothea Respa Kusumaningrat; Gisella Sekar Wruhastanti; Yohana Joni (Jurnal Rekonstruksi dan Estetik)
Highlights: